Ethanol intake of paediatric intensive care patients. Issue 6 (9th May 2013) - Isaac, R; Khan, I; Langley, C
Abstract : Background: Limiting the amount of alcohol in children's medicines is advisable but as alcohol is the second most common solvent used in liquid preparations, paediatric patients with increased medication intake may be exposed to a considerable alcohol intake. Few medicines are specifically designed for children in Paediatric Intensive Care (PICU), and therefore adult formulations are frequently administered, with high medication use further exposing a PICU patient to undesired alcohol intake. Aims: This small pilot study aimed to examiine the intake of a sample of PICU patients, highlight common medicines used on PICU containing alcohol, provide alternatives where possible and where alternatives are not possible, provide the prescriber with a list of the higher alcohol containing medicines. Method: A retrospective medication chart review was undertaken as a two point snap shot. Data collected included age, weight, medications prescribed and the formulations used at time of the study. The patients' sedation score was recorded. The electronic medicine compendium (EMC) was consulted for any ethanol content for the commercially available products. The manufacturer was contacted for ethanol content of all 'specials' and any commercial products found to contain ethanol from the EMC. The PICU patient's daily intake of ethanol was calculated. The calculation was converted to an adult equivalent alcohol unit intake and although this method of conversion is crude and does not take physiological differences of adult and children into account, it was done in order to provide the clinician with commonly used terminology in deciding the risk to the patient. Results: Twenty-eight patients were prescribed a range of 69 different medications. Of the 69 medicines, 12 products were found to contain ethanol. Patient ages ranged from a 26 week premature infant to 15 years old, weights ranges from 0.7 kg to 45 kg. Only 2 out of the 28 patients did not receive ethanol containing medications, and most patients were prescribed at least two medicines containing ethanol. Daily ethanol intake uncorrected for weight ranged from 0.006 ml to 2.18 ml (median 0.26 ml). Converting this to adult units per week, alcohol intake ranged from 0.07 to 15.2 units (median 1.4 units). The two patients receiving above 15 units/week adult equivalent were prescribed an oral morphine weaning regimen, therefore the high alcohol exposure was short term. The most common drugs prescribed containing alcohol were found to be nystatin, ranitidine, furosemide and morphine. No commercially available alcohol-free oral liquid preparations were found for ranitidine, furosemide or morphine at the time of the study. Correlation of the sedation score against ethanol intake was difficult to analyse as most patients were actively sedated. Conclusions: Polypharmacy in PICU patients increases the exposure to alcohol. Some commercially available medicines provide excessive ethanol intake, providing the clinician with ethical, potentially economical dilemmas of prescribing an unlicensed medicine to minimise ethanol exposure. Further research is required to evaluate the scope of the problem, effects of exposure and provision of alcohol free formulations.